Mercury distribution in a mangrove tidal creek affected by intensive shrimp farming - Costa, B. G. B. (2013)
from a mangrove creek that receives intensive shrimp farming effluents were determined. The average dissolved and particulate Hg concentrations in the water varied from 3.1 to 9.2 ng L-1 and from 4.4 to 9.4 ng L-1 , respectively. However, the Hg concentrations in the suspended particulate matter and the bottom sediments varied from 95.4 to 115.7 ng g-1 and from 1.6 to 10.3 ng g-1 , respectively. A Ward quadratic distance cluster analysis based on the Hg concentrations and hydro- and geochemical parameters (oxygen, salinity, temperature, pH, and organic matter and aluminum content) showed the effects of shrimp farming effluents on the Hg distribution pattern. Furthermore, these results were supported by the Hg distribution in the sediment cores. This study emphasizes the necessity of including Hg as a potential pollutant when monitoring the environmental impacts of intensive shrimp farming.